STRATEGI PENGEMBANGAN DESA WISATA BERBASIS MASYARAKAT DI DESA CAU BELAYU, TABANAN - Eka Mahadewi, Ni Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 10 No 2 (2022): Jurnal IPTA (December 2022), 2023)
This research is conducted because the development of tourism in Tabanan Regency is monotonous in its popular tourist attraction and there is no innovation to collaborate between the natural, cultural, and creative potential of the local community. One of the innovation breakthrough that needs to be done is the development of Community-Based Tourism Village in Cau Belayu Village, Marga District, Tabanan Regency. This study aims to formulate strategy model and program for the development of Community-Based Tourism Village in Cau Belayu Village, Marga District, Tabanan Regency. This study results indicate several strategies that can be applied: developing a variety of rural tourism products based on the uniqueness of the local potential, creating a brand image of tourist destinations, increasing marketing activities for rural tourism products, improving traditional village based security systems, increasing tourism industry product certification, implementing CHSE strict regulations in every presentation of rural tourism products and activities, strategies for strengthening the entrepreneurial spirit of the Cau Belayu Village community, strategies for building marketing networks with tourism stakeholders, creating smooth and beautiful accessibility to tourist attractions, building tourism institutional governance, creating beautiful environment in the area around tourist attractions, increasing the competence of human resources in the field of tourism, increasing public awareness of tourism awareness and Sapta Pesona.